Analisis Konten dan Engagement Video Fomo Kementerian Sosial di Tiktok - Ida Ayu Nyoman Sucindra Wira; I Ketut Putu Suardana; Rieka Yulita Widaswara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines the use of TikTok by the Indonesian Ministry of Social Affairs as a public communication medium for delivering educational messages related to the phenomenon of Fear of Missing Out (FOMO). FOMO has emerged as a relevant psychosocial issue in the era of social media, as young people are particularly vulnerable to anxiety, social pressure, and digital dependency. Therefore, adaptive and effective public communication strategies are required to address the characteristics of digital audiences. This research aims to describe the communication strategies employed by the Ministry of Social Affairs, identify the characteristics of video content that influence audience engagement, and interpret engagement metrics as representations of public interaction. A qualitative approach was adopted using content analysis, supported by observation, documentation, and a literature review. The analysis was grounded in the theories of Uses and Gratifications, Persuasive Communication, and Diffusion of Innovations. The findings indicate that short-form videos featuring authoritative narration, a problem-solution structure, and contrasting visuals are effective in attracting audience attention and encouraging appreciative engagement in the form of likes, saves, and shares. However, the absence of comments reflects limited dialogic interaction. This study concludes that the Ministry of Social Affairs’ public communication through TikTok is effective in disseminating educational information, yet it requires more interactive strategies to enhance the quality of audience participation.